1983
DOI: 10.1002/macp.1983.021841217
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR studies on n‐paraffins in restricted molecular motion

Abstract: The IH NMR spectra of guest molecules. n-paraffins (n-C,H,, , n-C6Hl, , n-c.,H16, n-GHzo, and n-C,H,), were measured in poly(y-benzyl-L-glutamate) liquid crystalline solution. The methylene signal of n-paraffins is a doublet due to magnetic dipole-dipole interaction. These results suggest that an n-paraffin takes predominantly the extended form in the restricted molecular motion state and that its long axis orients in the same direction as the helical axis of poly(y-benzyl-L-glutamate) parallel to the magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…According to our previous work on the orientation of n -alkanes in PBLG liquid crystalline state by 1 H NMR, in which PBLG chains are highly oriented, n -alkanes being guest molecules are highly oriented to the magnetic field of an NMR magnet with the relatively extended conformation along the α-helical PBLG chains. Also, as elucidated by NMR method, n -alkanes in the rotator phase take an extended conformation and are fastly rotating around the long axis, , and the diffusion coefficients for the direction in parallel and perpendicular to the long axis are different from each other .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous work on the orientation of n -alkanes in PBLG liquid crystalline state by 1 H NMR, in which PBLG chains are highly oriented, n -alkanes being guest molecules are highly oriented to the magnetic field of an NMR magnet with the relatively extended conformation along the α-helical PBLG chains. Also, as elucidated by NMR method, n -alkanes in the rotator phase take an extended conformation and are fastly rotating around the long axis, , and the diffusion coefficients for the direction in parallel and perpendicular to the long axis are different from each other .…”
Section: Introductionmentioning
confidence: 99%
“…Under such a background, we have been attracted to a research program how is the diffusional process of n-alkanes with the relatively extended conformation in the gel with anisotropic structure because of the fact that n-alkanes are basic molecules for understanding structure and dynamics of linear polymer chains. [8][9][10] According to our previous work on the orientation of n-alkanes in PBLG liquid crystalline state by 1 H NMR, 11 in which PBLG chains are highly oriented, n-alkanes being guest molecules are highly oriented to the magnetic field of an NMR magnet with the relatively extended conformation along the R-helical PBLG chains. Also, as elucidated by NMR method, n-alkanes in the rotator phase take an extended conformation and are fastly rotating around the long axis, 12,13 and the diffusion coefficients for the direction in parallel and perpendicular to the long axis are different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(γ‐benzyl L ‐glutamate) (PBLG) forms a lyotropic liquid‐crystalline phase in good solvents such as dichloromethane, 1,4‐dioxane, and chloroform,1–3 and it exhibits a sol–gel transition in N,N ‐dimethylformamide and benzyl alcohol 4–7. The PBLG chains in the lyotropic liquid‐crystalline phase are highly oriented in a magnetic field 8–13. Kishi et al14, 15 prepared PBLG gels in cholesteric and nematic liquid‐crystalline phases and then studied the properties of the obtained gels.…”
Section: Introductionmentioning
confidence: 99%
“…13 The observed Av is shown as a function of pressure in Figure 2. The NMR spectra were taken at 25 "C by using a JEOL PS-100 spectrometer (operating a t 100 MHz) equipped with a Fourier transform accessory.…”
mentioning
confidence: 99%
“…Thus, the separation is a function of the order parameter of the liquid crystal. 13 The observed Av is shown as a function of pressure in Figure 2. It is observed that Av increases with increasing pressure.…”
mentioning
confidence: 99%